Economic Viability of Raising Entire-rooted Transplants (ETPs) of Populus deltoides Marsh., in Nursery and Effect of Economies of Scale - Ramesh Singh, D. R.; Vashista, U. S. (Indian Forester, 2001)
Yamuna Nagar District has emerged as a leading district in the manufacture of wood based panel products utilizing plantation grown Populus and Eucalyptus wood. ETPs of Populus initially produced only by Forest Department are now being raised by enterprising persons also. The expenditure involved in raising ab initio nursery in one of the villages, namely, Thaska and the financial returns expected out of the sale of ETPs have been analysed and scenario of larger nursery from 0.4 ha to 1.0 ha which brings economy of scale into operation has been analyzed. It is concluded that nursery activity by resident farmers already practising agriculture on not less than 1.0 ha is economically a better proposition. Novices are advised to raise not less than one ha of nursery.